A PhD Is Not Enough: A Guide To Survival In Science - Feibelman, Peter J. (New York Basic Books, 1993)
Despite your graduate education, brainpower, and technical prowess, your career in scientific research is far from assured. Permanent positions are scarce, science survival is rarely part of formal graduate training, and a good mentor is hard to find. This exceptional volume explains what stands between you and fulfilling long-term research career. Bringing the key survival skills into focus, A Ph.D. Is Not Enough! proposes a rational approach to establishing yourself as a scientist. It offers sound advice of selecting a thesis or postdoctoral adviser, choosing among research jobs in academia, government laboratories, and industry, preparing for an employment interview, and defining a research program. This book will help you make your oral presentations effective, your journal articles compelling, and your grant proposals successful. A Ph.D. Is Not Enough should be required reading for anyone on the threshold of a career in science.